195 Angiotensin-(1-9) Reduces Cardiac Dysfunction in a Model of Angiotensin II-Induced Hypertensive Heart Disease. (6th June 2015) - Nather, Katrin; Nicklin, Stuart A; Loughrey, Christopher M; Touyz, Rhian M; Flores-Muñoz, Mónica; Wills, Lauren
Abstract : Angiotensin II (AngII) is involved in the pathophysiology of cardiovascular diseases including hypertension, myocardial infarction and heart failure. The counter-regulatory axis of the renin angiotensin system is centred on angiotensin-converting-enzyme 2 generating angiotensin-(1-7) which opposes the pathological actions of AngII in the heart. We recently showed that angiotensin-(1-9) [Ang-(1-9)] is part of the counter-regulatory axis which acts on the angiotensin type 2 receptor to inhibit AngII-induced cardiomyocyte hypertrophy in vitro and the development of cardiac fibrosis and hypertrophy in the stroke prone spontaneously hypertensive rat. 1 Here, we characterised chronic effects of AngII infusion on cardiac function in mice and assessed whether Ang-(1-9) can reverse AngII-induced cardiac pathology. In study 1, C57BL/6J mice were infused with H2 O (control), 24 μg/kg/hr or 48 μg/kg/hr AngII for 6 weeks via osmotic minipumps. A separate group was infused with Ang-(1-9) (48 μg/kg/hr) alone to assess direct effects on cardiac function. In study 2, mice were infused with H2 O or 48 μg/kg/hr AngII for 2 weeks, minipumps were replaced and mice received either H2 O, AngII or AngII with Ang-(1-9) for a further 2 weeks. Cardiac function was measured by echocardiography and histological staining for cardiac fibrosis and cardiomyocyte hypertrophy performed. After 6 weeks AngII infusion, fractional shortening (FS) was significantly decreased with either dose [control 45.5 ± 1.8%; AngII (24 μg) 32.3 ± 1.8%; AngII (48μg) 36.6 ± 4.2%; p < 0.05]. However, 48 μg AngII accelerated the decline in cardiac function causing an acute reduction in FS by 2 weeks. Cardiac hypertrophy [heart weight/tibia length (HW/TL)] significantly increased with either AngII dose [control 10.0 ± 0.3; AngII (24 μg) 11.4 ± 0.4; AngII (48 μg) 12.2 ± 0.3; p < 0.05]. Furthermore, increased cardiomyocyte hypertrophy was observed [control 22.6 ± 0.3 μm; AngII (24 μg) 26.1 ± 0.9 μm; AngII (48 μg) 26.8 ± 1.0 μm; p < 0.05]. Cardiac fibrosis, assessed via collagen I and III immunohistochemistry, revealed AngII caused a significant increase in collagen I [control 3.2 ± 0.5%; AngII (24 μg) 5.6 ± 0.6%; AngII (48 μg) 5.03 ± 0.4%; p < 0.05] and III [control 2.0 ± 0.2%; AngII (24 μg) 3.6 ± 0.4%; AngII (48 μg) 4.8 ± 0.8%; p < 0.05]. Infusion of Ang-(1-9) alone had no effect on FS, HW/TL, cardiomyocyte hypertrophy or collagen I and III deposition. When Ang-(1-9) was infused with AngII after an initial 2 week AngII infusion, mice showed a recovery in cardiac function as measured by FS (control 50.5 ± 2.2%; AngII 33.6 ± 1.9%; AngII+Ang-(1-9) 42.7 ± 4.1%). Further studies are ongoing to assess the effects of Ang-(1-9) beyond 2 weeks. These results demonstrate that Ang-(1-9) can limit AngII-induced cardiac dysfunction and therefore has therapeutic potential in a range of cardiovascular diseases. Reference: Flores-Munoz M et al . Hypertension. 2012;59(2):300-7